Faktor-faktor yang Mempengaruhi Kepatuhan Wajib Pajak Bumi dan Bangunan di Kabupaten Kendal - Mila Agustin; Ceacilia Srimindarti (Universitas Batanghari, 2023)
This study aims to analyze tax knowledge, taxpayer awareness, taxpayer attitudes, tax sanctions and tax socialization towards taxpayer compliance. The population of this study is land and building taxpayers in Kendal District. Determination of the sample with the Roscoe margin of error formula so that a sample of 100 respondents was determined. Primary data uses questionnaires shared via google forms and directly dating respondents. This research has theories and practical implications. This study used Multiple Linear Regression Analysis the results showed: 1.) Tax knowledge has no significant effect on taxpayer compliance. 2.) Taxpayer awareness has a significant positive effect on taxpayer compliance. 3.) The attitude of the taxpayer has no significant effect on the compliance of the taxpayer. 4.) Tax sanctions have a positive effect on taxpayer compliance. 5.) Socialization of taxation has a significant positive effect on taxpayer compliance.